Design of a communication system for multi-mobile robot coordination - Teo, Jasper Zheng Wei (Nanyang Technological University, 2020)
The executive summary of the report is to elaborate the intensive research, implement and discover the best communication method for multi-mobile robots as the primary focus. Firstly, ideation involves an intensive research. It includes exploring and narrowing the most appropriate communication tools for experimentation. Secondly, implementation. To experiment and collect feedback from the exercises of exchanging packets between the robots through various ways. Lastly, filter. After understanding the nature and implementation of each communication tool, the key challenge is to address the most suitable communication method for multi-mobile robots. Through the feedback that is collected from the experiments, this is the initial achievement towards a real life application of designing a communication system between multi-robot coordination.